Bimbingan Karir Dalam Meningkatkan Vocational Skills Remaja Putus Sekolah Di PSBR Yogyakarta - Adiansyah, Adiansyah (BKI IAIN Pontianak, 2022)
Adolescence is a phase in human development. Adolescents are in the child and adult phases. When teenagers behave like children, teenagers will be taught to act according to their age but if they behave like adults, they are often accused of being too big and even scolded for acting like adults. Teenagers experience confusion and even feel fear and difficulty in dealing with emerging phenomena and realities so it is a logical reason if teenagers should get an education. However, not all teenagers can get an education. Under certain circumstances, teenagers are forced to drop out of school. Disconnecting teenagers from formal education services in schools can certainly trigger more complex problems. One alternative is to provide guidance on non-formal pathways through the Yogyakarta Youth Foster Social Home (PSBR). This research aims to explore the problems experienced by teenagers who drop out of school and what career guidance provided by PSBR to improve vocational skills of adolescents out of school. Referring to the researcher's goal, the study uses a qualitatively de-de-approach by means of in-depth observations in analyzing data that later produces deriftive data from the observed object. Researchers found that adolescents dropping out of school at PSBR experience educational problems, career or work problems and marital or married living problems. Skills are carried out with two models, namely by providing theory and then continued with guidance in the form of practice. Some of the skills that are called include cosmetology / salon skills, sewing skills, furniture / wood skills, machine skills / motorcycle mechanic and welding skills.